Peran Public Relations Dalam Meningkatkan Brand Awareness (Studi Kasus Instagram @Mashumas_ Pt Kai Daop 1 Jakarta) - Syafitri, Dinda Nur; Priatna, Wahyu Budi (Jurnal Multidisiplin Dehasen (MUDE), 2025)
The development of digital technology has transformed the landscape of communication between companies and the public, particularly in efforts to build brand awareness through social media. This study aims to understand the role of Public Relations in increasing brand awareness through the Instagram account @mashumas_ managed by PT KAI DAOP 1 Jakarta. The research employs a qualitative approach using a case study method. Data collection techniques include in-depth interviews with three informants from the Public Relations team, non-participant observation of social media content, and supporting documentation. The results show that the Public Relations team at PT KAI DAOP 1 Jakarta implements a well-planned digital communication strategy, such as creating visually appealing and informative content, actively engaging with the audience, and analyzing engagement data as a basis for evaluation and strategy development. The role of Public Relations is highly significant in shaping a positive corporate image and strengthening relationships with the public through social media. These findings indicate that strategic management of social media by the Public Relations team can enhance brand awareness and reinforce the company’s position in the transportation industry. Therefore, developing the digital capacity of the Public Relations team and strengthening the synergy between visual content and data analysis are essential steps in formulating an effective and sustainable communication strategy.